2008
DOI: 10.1016/j.ygyno.2007.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Binding Protein 1 expression in ovaries and ovarian tumors in the laying hen, a spontaneous model of human ovarian cancer

Abstract: Objective-Reduced Selenium-Binding Protein 1 (SELENBP1) expression was recently shown in multiple cancers. There is little information on the expression and function of SELENBP1 in cancer progression. In order to develop a better understanding of the role of SELENBP1 in ovarian cancer, our objective was to determine if SELENBP1 is expressed in the normal ovaries and ovarian tumors in the egg-laying hen, a spontaneous model of human ovarian cancer.Methods-SPB1 mRNA expression in normal ovary (n=20) and ovarian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 44 publications
1
33
1
Order By: Relevance
“…We were able to demonstrate a differential expression of SELENBP1 in various histologic components within SBOT. Although a decreased expression of SELENBP1 was previously described in high-grade ovarian serous carcinoma of the human subjects [4] and of the experimental hens [11], our study showed a reduction of SELENBP1 expression in LGSC of the human ovary.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We were able to demonstrate a differential expression of SELENBP1 in various histologic components within SBOT. Although a decreased expression of SELENBP1 was previously described in high-grade ovarian serous carcinoma of the human subjects [4] and of the experimental hens [11], our study showed a reduction of SELENBP1 expression in LGSC of the human ovary.…”
Section: Discussioncontrasting
confidence: 80%
“…By membrane proteome profiling analysis, SELENBP1 was found to be the most significantly down-regulated protein in ovarian cancer cells [4]. Down-regulation of SELENBP1 was also demonstrated in ovarian carcinomas in the experimental laying hens [11]. To date, however, no systematic studies have been carried out concerning the expressions of SELENBP1 in SBOT, M-SBOT, and LGSC.…”
Section: Introductionmentioning
confidence: 99%
“…Although a physiological function has not yet been assigned to SBP1, its involvement in detoxification mechanisms is largely suggested. Downregulation of SBP1 expression is correlated with rapid tumor development in many organs (Kim et al, 2006;Stammer et al, 2008), and recently, SBP1 was characterized as a biomarker for schizophrenia (Glatt et al, 2005). Moreover, its homolog SBP2 is suggested to play a protective role as a scavenger of toxic electrophiles or oxidant species (Lanfear et al, 1993;Cohen et al, 1997;Mattow et al, 2006).…”
mentioning
confidence: 99%
“…The histology, biochemistry, genetic mutations, and tumor immunology in this model have striking similarities with human ovarian tumors (Rodriguez-Burford et al 2001, Barua et al 2009a, Barua et al 2009b, Hakim et al 2009, Gonzalez Bosquet et al 2010, Bradaric et al 2013). Both anti-SBP1 (Stammer et al 2008) and anti-mesothelin (Yu et al 2011) are associated with reduced ovarian function and with ovarian tumors in the hen.…”
Section: Discussionmentioning
confidence: 99%